(untitled) (Journal of the College of Basic Education, 2026)
The speech of the infallible Imams of the Household (peace be upon them) is characterized by its high eloquence. Their speech contains much of the Qur’anic influence, in addition to its scholarly value and profound wisdom. This research sheds light on the art of speech in the words of Imam al-Rida (peace be upon him). The research examines a type of his noble speech: the art of signatures. The reason that prompted us to study it is that his signatures contain various rhetorical arts, including the art of brevity, precedence and postponement, and rhetorical devices, especially semantic embellishments. Imam al-Rida (peace be upon him) employed the art of antithesis. Furthermore, the researcher of the Imam’s signatures will notice that they contain eloquent and moving wisdom, as they emanate from an infallible Imam whose obedience is obligatory, and that these timeless sayings are suitable for all ages and times.